Breakthrough Listen follow-up of the reported transient signal observed at the Arecibo Telescope in the direction of Ross 128 - Enriquez, J.; Siemion, A.; Dana, R.; Croft, S.; Méndez, A.; Xu, A.; DeBoer, D.; Gajjar, V.; Hellbourg, Gregory; Isaacson, H.; others (2017)
We undertook observations with the Green Bank Telescope, simultaneously with the 300 m telescope in Arecibo, as a follow-up of a possible flare of radio emission from Ross 128. We report here the non-detections from the GBT observations in C band (4–8 GHz), as well as non-detections in archival data at L band (1.1–1.9 GHz). We suggest that a likely scenario is that the emission comes from one or more satellites passing through the same region of the sky.